Antagonistic modules regulate photosynthesis-associated nuclear genes via GOLDEN2-LIKE transcription factors. Issue 4 (24th December 2021) - Li, Mengping; Lee, Keun Pyo; Liu, Tong; Dogra, Vivek; Duan, Jianli; Li, Mengshuang; Xing, Weiman; Kim, Chanhong
Abstract: GOLDEN2-LIKE (GLK) transcription factors drive the expression of photosynthesis-associated nuclear genes (PhANGs) indispensable for chloroplast biogenesis. Salicylic acid (SA)-induced SIGMA FACTOR-BINDING PROTEIN 1 (SIB1), a transcription coregulator and positive regulator of cell death, interacts with GLK1 and GLK2 to reinforce the expression of PhANGs, leading to photoinhibition of photosystem II and singlet oxygen ( 1 O2 ) burst in chloroplasts. 1 O2 then contributes to SA-induced cell death via EXECUTER 1 (EX1; 1 O2 sensor protein)-mediated retrograde signaling upon reaching a critical level. This earlier finding has initiated research on the potential role of GLK1/2 and EX1 in SA signaling. Consistent with this view, we reveal that LESION-SIMULATING DISEASE 1 (LSD1), a transcription coregulator and negative regulator of SA-primed cell death, interacts with GLK1/2 to repress their activities in Arabidopsis ( Arabidopsis thaliana ). Overexpression of LSD1 repressed GLK target genes, including PhANGs, whereas loss of LSD1 enhanced their expression. Remarkably, LSD1 overexpression inhibited chloroplast biogenesis, resembling the characteristic glk1glk2 double mutant phenotype. Subsequent chromatin immunoprecipitation coupled with expression analyses further revealed that LSD1 inhibits the DNA-binding activity of GLK1 toward its target promoters. SA-induced nuclear-targeted SIB1 proteins appeared to interrupt the LSD1–GLK interaction, and the subsequent SIB1–GLK interaction activated EX1-mediated 1 O2 signaling, elucidating antagonistic modules SIB1 and LSD1 in the regulation of GLK activity. Taken together, we provide a working model that SIB1 and LSD1, mutually exclusive SA-signaling components, antagonistically regulate GLK1/2 to fine-tune the expression of PhANGs, thereby modulating 1 O2 homeostasis and related stress responses. Abstract : Salicylic acid-related transcription coregulators interact with GLK transcription factors to modulate chloroplast ROS homeostasis.